2008
DOI: 10.1080/00036840600905134
|View full text |Cite
|
Sign up to set email alerts
|

International fish trade and exchange rates: an application to the trade with salmon and fishmeal

Abstract: International fish trade is growing, and fish exports represent an important source of foreign currency for many countries. For a few countries the exports are also an essential part of the economy. We revisit the seminal paper of Richardson (1978) that addresses the issue of exchange rate pass-through in commodity markets, but in a multivariate cointegration framework. The multivariate cointegration framework allows us to test common assumptions like exchange rate pass-through, leading price, central markets,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…This is given by the Fish Pool price index, FPI TM (Fish Pool, 2014). The index is based on prices for different sizes of salmon and at different levels in the supply chains, utilizing the fact that different salmon markets are well integrated with a high degree of price transmission (Tveterås & Asche, 2008;Asche et al, 2014) to provide a broad base for the index. This construct also avoids the grading issue, as the price is always the average price and one does not have to take delivery of a grade one does not want as was the case for shrimp.…”
Section: Data and The Fish Pool Exchangementioning
confidence: 99%
“…This is given by the Fish Pool price index, FPI TM (Fish Pool, 2014). The index is based on prices for different sizes of salmon and at different levels in the supply chains, utilizing the fact that different salmon markets are well integrated with a high degree of price transmission (Tveterås & Asche, 2008;Asche et al, 2014) to provide a broad base for the index. This construct also avoids the grading issue, as the price is always the average price and one does not have to take delivery of a grade one does not want as was the case for shrimp.…”
Section: Data and The Fish Pool Exchangementioning
confidence: 99%
“…Price variations have several sources, creating unstable equilibriums with supply variations due to factors such as seasonality and production shocks and demand variations due to e.g., changes in the supply of close substitutes. Moreover, international trade is substantial for seafood, with 39% of fish production traded and around 77% exposed to trade (Tveterås et al, 2012), contributing further factors to influence price volatility such as trade barriers and exchange rates (Tveteras & Asche, 2008). Dahl and Oglend (2014) showed that in aggregate, prices of fish from aquaculture are less volatile than wild fish, and also reported volatility measures for different species groups.…”
Section: Introductionmentioning
confidence: 98%
“…5 There has been little focus on the impact of exchange rate movements in the seafood literature in general. Tveterås and Asche (2008) show that exchange rates do not impede market efficiency for salmon and fishmeal, while Larsen and Kinnucan (2009) show efficient price transmission for salmon. Xie, Kinnucan, and Myrland (2009) show that exchange rate movements are split according to slopes of the demand and supply schedules.…”
Section: Notesmentioning
confidence: 99%